SPATIALIZED SEQUENTIAL WATER CLIMATOLOGICAL BALANCE FOR DROUGHT MONITORING OF RIO DO PEIXE BASIN - SC - Linheira, Guilherme; Oliveira, Francisco Henrique de; Santo, Mariane Alves Dal; Rampazzo, Sônia Elisete; Gerente, Jéssica; Pandolfo, Cristina; Ricce, Wilian da Silva (Revista Brasileira de Cartografia, 2015)
This research investigates the relation between registered damages due to drought and monthly value occurrences of hydric deficit, calculated by the Climatological Water Balance Sequential. The study area is Rio do Peixe Basin located at western of Santa Catarina State (South of Brazil). It was made the Climatological Water Balance Sequential for 2001-2010 period, considering three stations located inside and nearby Rio do Peixe Basin. From this Climatological Water Balance it was noticed that the highest hydrous deficits occurred in these short periods: February and March of 2005, April and May of 2006 and March and April of 2009. Afterwards, it was related the hydrous deficit values with official damage registers by drought called "AVADAN". In fact the results characterized the correlations between registered damages due to drought and monthly value occurrences of hydric deficit. Besides, in the three drought periods, the year 2009 was defined as a special sample to spatialized the damage occurrences by (AVADAN) documents and hydric deficit registered in the meteorological stations. The year 2009 was selected due the fact that 92% of the municipalities within the Rio do Peixe Basin registered of damage by drought. For generate the surface in the Rio do Peixe Basin area it was interpolate data by mathematic model called Exponential Kriging. The result guided to confirm the correlation between negative values of Climatological Water Balance Sequential and AVADANs in effective way. It is recommended apply this methodology in others basins as procedure to validate it.